Psychometric properties of the Care Dependency Scale in stroke survivors in Indonesian hospitals - Nursiswati Nursiswati; Ruud J.G. Halfens; Christa Lohrmann (Elsevier, 2020)
Purpose: This study aimed to evaluate the psychometric properties of the Indonesian version of the Care Dependency Scale (CDS) among stroke survivors. Methods: The study was undertaken in four hospitals. We analysed datasets obtained from 109 stroke survivors on inpatient wards and in outpatient clinics, who were rated by nurses to determine the CDS reliability coefficients. The Cronbach's α and Cohen's kappa coefficients were applied. Concurrent validity was conducted for the data on care dependency, which werecollected from 49 of these 109 participants on inpatient wards by nurses using the CDS and the Barthel Index. A Spearman's rank correlation analysis was conducted to measure the association between the CDS and the Barthel Index results. Results: An analysis of the results of the CDS tested on the inpatient ward and in the outpatient clinic revealed a high level of internal consistency. The reliability analysis yielded the same Cronbach's α coefficient of 0.98 for both the inpatient and outpatient data. A significant, moderate correlation was observed between the CDS and Barthel Index results. Conclusion: The CDS can be recommended for use as a tool for the assessment and evaluation of stroke survivors who are receiving acute or long-term care.